2004
DOI: 10.1002/hep.20060
|View full text |Cite
|
Sign up to set email alerts
|

Detection and identification of tumor-associated protein variants in human hepatocellular carcinomas

Abstract: The proteomic approach is a valuable tool to detect and identify proteins that are associated with cancer. In previous investigations on experimentally induced rat hepatomas, we detected aldose reductase-like protein (ARLP) as a highly significant marker protein. Our present study was intended to look for the presence of similar tumor-associated marker proteins on human hepatocellular carcinomas (HCC). We found several novel tumorassociated protein variants that represent members of the aldo-keto reductase (AK… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
71
0

Year Published

2005
2005
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 101 publications
(75 citation statements)
references
References 49 publications
4
71
0
Order By: Relevance
“…Several reports have shown that over-expression of AR in many tumor cells renders these cells resistant to chemotherapy and also demonstrate that inhibition of AR enhances sensitivity to chemotherapeutic drugs. 40,52,53 CONCLUSION Present data clearly demonstrate the chemo-sensitizing benefit of AA and DAS combination to CP therapy. These natural substances potentiated the effect of CP on almost all the parameters that could be affected in the course of hepatocarcinogenesis.…”
Section: Discussionsupporting
confidence: 55%
“…Several reports have shown that over-expression of AR in many tumor cells renders these cells resistant to chemotherapy and also demonstrate that inhibition of AR enhances sensitivity to chemotherapeutic drugs. 40,52,53 CONCLUSION Present data clearly demonstrate the chemo-sensitizing benefit of AA and DAS combination to CP therapy. These natural substances potentiated the effect of CP on almost all the parameters that could be affected in the course of hepatocarcinogenesis.…”
Section: Discussionsupporting
confidence: 55%
“…Briefly, culture cells or tissues were lysed in buffer containing 10 mmol/l Tris (pH 7.4), 1% sodium dodecyl sulfate (SDS), 1 mmol/l sodium orthovanadate, and complete protease inhibitors (Roche). The extraction was accomplished using the Klose method as described previously (22,23). Samples of the lysates (50 µg) were then separated using SDS-polyacrylamide gel electrophoresis (SDS-PAGE), transferred to polyvinylidene fluoride membranes (Millipore, Bedford, MA), and blotted with the primary antibodies.…”
Section: Rna Isolation Reverse Transcription-polymerase Chain Reactimentioning
confidence: 99%
“…Most of the AKR superfamily proteins are involved in the detoxification of a wide variety of substrates. Several reports have shown that over-expression of AR, in many tumor cells, renders these cells resistant to chemotherapy, and also demonstrate that inhibition of AR enhances cancer cell sensitivity to chemotherapeutic drugs [56,57] . In addition, over-expression of AR enhances production of ROS, which cause membrane damage and cellular leakage [58] .…”
Section: Ibrahim Ss Et Al Das and Ndea Induced Liver Carcinogenesismentioning
confidence: 99%